Perigomphus basicornis sp. nov. (Odonata: Gomphidae) from Anchicayá, Colombia - Amaya-Vallejo, Vanessa; Novelo-Gutiérrez, Rodolfo; Realpe, Emilio (Zootaxa, 2017)
The new sp. is described and illustrated based on adult males obtained from mature larvae collected in Anchicayá zone, Valle del Cauca, Colombia, and reared in Universidad de Los Andes laboratory, Bogotá, Colombia. The adult differs from the other described species of Perigomphus in the shape of the cerci and the size of the epiproct. Larvae are easy to collect in field but challenging to rear in the lab because of their habitat preferences. Adults are difficult to find in the field as they live high in the canopy. Holotype: reared male and exuviae, 22.xi.2016; deposited in Instituto de Ecología, A.C., Xalapa, Mexico.